A Systematic Analysis of the Radio Properties of 22 X-Ray-selected Tidal Disruption Event Candidates with the Australia Telescope Compact Array - A. J. Goodwin; M. Burn; G. E. Anderson; J. C. A. Miller-Jones; I. Grotova; P. Baldini; Z. Liu; A. Malyali; A. Rau; M. Salvato (The Astrophysical Journal Supplement Series)
We present a systematic analysis of the radio properties of an X-ray-selected sample of tidal disruption event (TDE) candidates discovered by the eROSITA telescope. We find radio sources coincident with half of the transient events (11 TDEs), with eight radio sources showing statistically significant variability over a 6 month period. We model the radio spectra of six sources with sufficiently bright radio emission and find the sources show radio spectra consistent with optically thin synchrotron emission and radio outflow minimum radii of 10 ^16 –10 ^17 cm, velocities 0.01 c –0.05 c , and energies 10 ^48 –10 ^51 erg. On comparison with the radio properties of an optically selected TDE sample at similar late times, we find no significant difference in the radio luminosity range or radio detection rate. We find a tentative positive trend with peak radio and X-ray luminosity, but require further observations to determine if this is real or due to observational bias due to the large range in distances of the events. Interestingly, none of the X-ray-selected events show late-rising radio emission, compared to 45% of radio-detected sources of an optically selected sample that showed late-rising radio emission. We propose that this may indicate that many TDEs launch radio outflows at or near peak X-ray luminosity, which can be significantly delayed from peak optical luminosity. This study presents the first systematic analysis of the radio properties of an X-ray-selected sample of TDEs, and gives insight into the possible link between the physical processes that power X-ray and radio emission in TDEs.